Two Cultures of Religion as Obstacles to Peace - Boulding, Elise (Zygon, 1986)
Abstract. There are two contrasting cultures in every religious tradition, the holy war and peaceable garden cultures. Examples are given for Christianity, Judaism, and Islam. Conflict is basic to human existence, stemming from the uniqueness of human individuals and their groups. Churches, instead of helping their societies develop the middle-ground skills of negotiation and mediation, have insisted on a choice between two extreme behaviors: unitive love or destruction of the enemy. In international affairs this has led to the identification of the church with the state in wartime and kept it from claiming the important middle ground of peacemaking. Institutionalized religion can pick up its missed opportunities.